Effects of friction stir welding on microstructure and mechanical properties of magnesium alloy Mg-5Al-3Sn. (15th November 2016) - Pan, Fusheng; Xu, Anlian; Deng, Dean; Ye, Junhua; Jiang, Xianquan; Tang, Aitao; Ran, Yang
Abstract: Mg-Al-Sn alloys are being developed as a new series of magnesium alloys due to good properties without any rare earth components. In order to investigate the effects of friction stir welding (FSW) on microstructures and mechanical properties of Mg-5Al-3Sn magnesium alloy, the hot-extruded alloy plates were butt welded by FSW at various welding speeds. The results showed that the alloy was jointed without defects. After FSW, β-Mg17 Al12 phase was dissolved into α-Mg matrix while Mg2 Sn phase with high dissolution point and good thermal stability remained in the nugget zone (NZ). With increasing welding speed, the maximum (0002) pole intensity in the NZ first decreased and then increased, and grain size of α-Mg matrix decreased arising from lower heat input while some intermetallic particles coarsened at higher welding speed due to solid state diffusion and less applied stress. In all cases the tensile properties of the alloy after FSW decreased due to the softened region at the heat-affected zone (HAZ), the dissolution of β-Mg17 Al12 phase, the residual stress and dislocation content in the TMAZ, the textural variation and the secondary phase changes. The elastic behavior of weld joints was different from the BM due to the dissolution of β-Mg17 Al12 particles. Graphical abstract: Mg-Al-Sn alloys are being developed as a new series of magnesium alloys due to good properties without any rare earth components. In order to investigate the effects of friction stir welding (FSW) on microstructures and mechanical properties of Mg-5Al-3Sn magnesium alloy, the hot-extruded alloy plates were butt welded by FSW at various welding speeds. The results showed that the alloy was jointed without defects. After FSW, β-Mg17 Al12 phase was dissolved into α-Mg matrix while Mg2 Sn phase remained in the nugget zone (NZ). With increasing welding speed, the maximum (0002) pole intensity in the NZ first decreased and then increased, and grain size of α-Mg matrix decreased while some intermetallic particles coarsened at higher welding speed. In all cases the tensile properties of the alloy after FSW decreased due to the softened region at the heat-affected zone (HAZ), the dissolution of β-Mg17 Al12 phase, the residual stress and dislocation content in the TMAZ, the textural variation and the secondary phase changes. The elastic behavior of weld joints was different from the BM due to the dissolution of β-Mg17 Al12 particles. Highlights: β-Mg17 Al12 phase was dissolved while Mg2 Sn phase remained after friction stir welding, for Mg-5Al-3Sn magnesium alloy. The elastic behavior of weld joints was different from the BM due to the dissolution of β-Mg17 Al12 particles. The maximum (0002) pole intensity in the NZ first decreased and then increased with increasing welding speed.